The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1159/000048694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Noncompetitive NMDA Antagonists MK-801 and Ketamine on the <i>Spastic</i> Han-Wistar Mutant: A Rat Model of Excitotoxicity

Abstract: The neuroprotective effects of the NMDA antagonists MK-801 and ketamine were analyzed in a mutant strain of Han-Wistar rats which develop neurodegeneration in the hippocampus and cerebellum. Previous experiments have shown that the progressive neuronal degeneration observed in this mutant may be the result of a dysfunctional glutamatergic system. For MK-801 studies, mutants were injected in a chronic paradigm with (+)MK-801 or its weaker acting isomer (–)MK-801 at a dose of 1 mg/kg. Ketamine studies consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Previously, this mutant rat model has been used for neural studies exclusively (7,39,44). The mechanical properties of the spastic rat calf muscles found in the present study are consistent with the reduced functional range of motion and increased stiffness reported clinically in human limbs affected by spasticity (17,31,32,40), and the narrower active lengthforce curves estimated in in vivo studies on human GA (2,15,16).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previously, this mutant rat model has been used for neural studies exclusively (7,39,44). The mechanical properties of the spastic rat calf muscles found in the present study are consistent with the reduced functional range of motion and increased stiffness reported clinically in human limbs affected by spasticity (17,31,32,40), and the narrower active lengthforce curves estimated in in vivo studies on human GA (2,15,16).…”
Section: Discussionsupporting
confidence: 90%
“…At 42-50 days postnatal, spastic paresis is manifested by limb rigidity and more plantar-flexed paws (37), which is also typical in humans with spastic lower legs. The spastic mutant rat has previously been used for neurophysiological studies (7,8,39,44), but the mechanical properties of its skeletal muscles have never been investigated.…”
mentioning
confidence: 99%
“…Some studies (145)(146)(147), though not all (148,149), suggest that NMDA antagonists trigger presynaptic release of glutamate, which, in turn, binds to AMPA receptors. No matter what the underlying mechanism, the apparent linkage between NMDA antagonism and AMPA receptor activation may help clarify how ketamine can be neuroprotective (150,151) in some contexts but potentially neurotoxic (151)(152)(153) in others. The necessity of AMPA activation implies that ketamine induces synaptogenesis by increasing glutamate signaling rather than by protecting neurons from glutamate excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Brunson et al (2001), it was demonstrated that ketamine has a neuroprotective effect in the hippocampus and cerebellum of a mutant strain of rat. On the contrary, in a study performed by Rudin et al (2005), a single dose ketamine administration to 7-dayold mice (neonatal) was shown to induce apoptosis in both the sensorimotor cortex and cerebellum.…”
Section: Introductionmentioning
confidence: 99%